Introduction to Space Archaeology - Guo, Huadong. author. aut Link
XIV, 403 p. 116 illus., 102 illus. in color.
Keywords: This book presents the basic principles and the latest advances in space archaeology. Following general reviews of the state of the art of Earth observation technologies and archaeology, the book introduces the principles and methods of space archaeology, remote sensing methods for archaeological survey, and integrated archaeological survey methods including geophysics, virtual reality, web technologies, global positioning systems (GPS), geographical information systems (GIS), and big data. The book then presents two chapters on case studies of word heritage sites in Asia, Europe, Africa, and Americas, including three major world heritage sites in China: The Great Wall, Grand Canal, and Silk Road. The last chapter of the book discusses the future of space archaeology. This book has an interdisciplinary appeal and scholars with an interest in cultural heritage and remote sensing technologies for Earth value its contribution.